Consumer Behaviour: Understanding Buying Behavior and Retaining Customers (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Companies make investment in understanding consumerbehaviour and implementing strategies, which will help them retain customers. Consumers can be categorized as an individual consumerand organizational/industrial consumers. Understanding their behaviour andbuying pattern is important in ultimate survival of companies in the marketplace. Consumer behaviourconsists of activities/process followed in making any buying decision of goodsas well as a service. In recent time service (holiday,travel, etc.), decisions are forming large part of consumer behaviour. One thing needs to be highlighted here is that consumerbehaviour does not end with purchase of goods or service, but also postpurchase activities are included in consumer behaviour. Consumer behaviourand consumption behaviour are two different concepts developed and cannot beused as a substitute. Consumer behaviour deals with the process of anindividual or organization in coming to the purchase decision, whereasconsumption behaviour is a study focus on consuming unit or service. Understanding of theconsumer behaviour begins with study of the consumer buying process. Consumerbuying process is five step activities. The starting with need recognition, which leads to information search, once informationis obtained from different sources next step, is the evaluation and intent where in consumer evaluates variousparameters of the product or service. The next step in five-step activity is the purchase decision where in intentis converted into an actual purchase of the good or the service. The final stepis post-purchase reaction wherein customer if she is satisfied with goods or services recommends to otherprospective customers or repeat the purchase. If the customer is not happy withpurchase, a bad word of strategies, which will help themretain customers.